The evolution of guideline-directed medical therapy among decompensated HFrEF patients in sacubitril/valsartan era: Medical expenses and clinical effectiveness. Issue 6 (2nd June 2021) - Liang, Huai-Wen; Liao, Chia-Te; Lin, Wen-Yu; Chung, Fa-Po; Huang, Jin-Long; Lee, Ying-Hsiang; Lin, Po-Lin; Chiou, Wei-Ru; Hsu, Chien-Yi; Chang, Hung-Yu
Abstract : Background: Over recent years, new evolution in guideline-directed medical therapy (GDMT) contributes to clinical benefits in patients with heart failure and reduced ejection fraction (HFrEF). The additional medical expenditure may be a concern due to the current financial constraint. This study aimed to investigate the medical costs and clinical effectiveness of contemporary GDMT in recently hospitalized HFrEF patients. Methods: Acutely decompensated hospitalized HFrEF patients from two multicenter cohorts of different periods were retrospectively analyzed. A propensity score matching was performed to adjust the baseline characteristics. Annual medication costs, risks of mortality, and recurrent heart failure hospitalizations (HFH) were compared. Results: Following 1:2 propensity score matching, there were 426 patients from the 2017-2018 cohort using sacubitril/valsartan, while 852 patients from 2013 to 2014 did not use so at discharge. Baseline characteristics were similar, whereas the sacubitril/valsartan users were more likely to receive beta-blockers, ivabradine and mineralocorticoid receptor antagonists at discharge (79.3% vs 60.4%, 23.2% vs 0%, and 64.1% vs 49.8%, p < 0.001). The 2017-2018 cohort produced more medication costs by 1277 United States dollar (USD) per person per year, while it resulted in lower rates of HFH and all-cause mortality (10.3 vs 20.3 and 48.8 vs 79.9 per 100 person-year, p < 0.001). Costs of preventing a mortality event and a HFH event with contemporary treatments were 15 758 USD (95% confidence interval [CI] 10 436-29 244) and 5317 USD (95% CI 3388-10 098), respectively. Conclusion: The higher adoption of GDMT was associated with greater medical expenses but better clinical outcomes in recently decompensated HFrEF patients.